Tradução e adaptação transcultural do Minnesota Handwriting Assessment para aplicação no Brasil - Pasculli, Adriane Guzman [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Writing is a typical hand human skill, which is essential for individuals to integrate and adapt to the social environment. It is a fairly complex skill that involves a combination of perceptual, motor, kinesthetic and cognitive components. The assessment of writing is one of the several challenges encountered by teachers in the literacy process. The present study aimed to validate and adapt transculturally, for the Brazilian context, the Minnesota Handwriting Assessment (MHA), an instrument developed by Judith Reisman and used in the United States of America. Participated in the study 448 children enrolled in the 2nd and 3rd school years from the public school system and two school teachers who served as examiners. The validation method proposed was the Cross-Cultural Adaptation and was applied for the validation only of the discrete D’Nealian style of handwriting. First, the equivalence of concepts, semantics and resulting idiomatic translation and retranslation of the MHA was done. Then, trustworthiness of this instrument for assessing the quality of the writing was verified. Next, children were asked to copy a sentence with all letters of the Brazilian alphabet. Finally, two teachers applied the adapted instrument for validation. The Intraclass Correlation Coefficient (ICC) for the trustworthiness test-retest was 0.92 for readability, 0.90 for form, 0.99 for alignment and 0.89 for spacing, being significant in all categories. With respect to reliability among evaluators, the ICC was 0.89 for readability, 0.99 for alignment, 0.98 for size, and 0.90 for spacing, reaching level of significance in these categories. The ICC 0,53 of form category did not reach level of significance what can be related to variability of the handwriting pattern of the Brazilian children. The cross-cultural adaptation proposed and the satisfactory results obtained from the validation of the discrete D’Nealian style of handwriting allow for the statement...

A escrita é uma habilidade manual típica do ser humano, indispensável para que o indivíduo se integre e se adapte ao meio social. É uma habilidade bastante complexa que envolve uma combinação de componentes perceptivos, motores, cinestésicos e cognitivos. A avaliação da escrita é o primeiro desafio encontrado pelas professoras que atuam no processo de alfabetização. O presente estudo teve como objetivo validar e adaptar transculturalmente, para o contexto brasileiro, o Minnesota Handwriting Assessment (MHA), instrumento elaborado por Judith Reisman e utilizado nos Estados Unidos da América do Norte para avaliação da qualidade da escrita manual. Participaram do estudo 448 crianças matriculadas nos 2º e 3º anos do sistema público de ensino e duas professoras de escola que foram examinadoras. O método de validação proposto foi o “Cross-Cultural Adaptation” e a validação foi feita com base no estilo de escrita de forma. Em um primeiro momento, foi realizada a equivalência de conceitos, semântica e idiomática resultantes da tradução e retradução do MHA. A seguir, a fidedignidade desse instrumento de avaliação da qualidade da escrita foi verificada pelo Coeficiente de Correlação Intraclasse (CCI). Posteriormente, as crianças foram solicitadas a copiar uma frase com todas as letras do alfabeto brasileiro. Finalmente, duas professoras aplicaram o instrumento traduzido e adaptado para validação do mesmo. O CCI do teste-reteste foi 0,92 para legibilidade, 0,90 para forma, 0,99 para alinhamento e 0,89 para espaçamento, sendo significativo em todas as categorias. Com relação a fidedignidade entre avaliadores, o CCI foi 0,89 para legibilidade, 0,99 para alinhamento, 0,98 para tamanho e 0,90 para espaçamento, alcançando nível de significância em todas estas categorias. O CCI da categoria forma foi 0,53, não atingindo nível de significância, resultado esse que pode estar relacionado à variabilidade do padrão...
Keywords: Minnesota Handwriting Assessment; Project method in teaching; Metodo de projeto no ensino; Escrita; Alfabetização; Estudos de validação; Avaliação educacional - Brasil